Final answer:
To solve 13 = (g/3) + 4, subtract 4 from both sides to obtain 9 = g/3 and then multiply by 3 to find g = 27. The solution g = 27 is not among the multiple-choice options, indicating a potential issue with the question.
Step-by-step explanation:
The solution to the equation 13 = (g/3) + 4 involves isolating the variable g. First, subtract 4 from both sides of the equation to get 9 = g/3. Then, multiply both sides by 3 to solve for g, which gives us g = 27. However, this solution was not listed in your multiple-choice options, indicating a possible typo in the question. Of the options provided, none match the correct solution of g = 27. If g must be one of the provided options, then the question as posed contains an error.